ACE inhibitors, angiotensin receptor blockers and endothelial injury in COVID‐19. (6th December 2020) - Tetlow, S.; Segiet‐Swiecicka, A.; O'Sullivan, R.; O'Halloran, S.; Kalb, K.; Brathwaite‐Shirley, C.; Alger, L.; Ankuli, A.; Baig, M.S.; Catmur, F.; Chan, T.; Dudley, D.; et al.
Abstract: Background: COVID‐19 is caused by the coronavirus SARS‐CoV‐2, which uses angiotensin‐converting enzyme 2 (ACE‐2) as a receptor for cellular entry. It is theorized that ACE inhibitors (ACE‐Is) or angiotensin receptor blockers (ARBs) may increase vulnerability to SARS‐CoV‐2 by upregulating ACE‐2 expression, but ACE‐I/ARB discontinuation is associated with clinical deterioration. Objective: To determine whether ACE‐I and ARB use is associated with acute kidney injury (AKI), macrovascular thrombosis and in‐hospital mortality. Methods: A retrospective, single‐centre study of 558 hospital inpatients with confirmed COVID‐19 admitted from 1 March to 30 April 2020, followed up until 24 May 2020. AKI and macrovascular thrombosis were primary end‐points, and in‐hospital mortality was a secondary end‐point. Results: AKI occurred in 126 (23.1%) patients, 34 (6.1%) developed macrovascular thrombi, and 200 (35.9%) died. Overlap propensity score‐weighted analysis showed no significant effect of ACE‐I/ARB use on the risk of occurrence of the specified end‐points. On exploratory analysis, severe chronic kidney disease (CKD) increases odds of macrovascular thrombi (OR: 8.237, 95% CI: 1.689–40.181, P = 0.009). The risk of AKI increased with advancing age (OR: 1.028, 95% CI: 1.011–1.044, P = 0.001) and diabetes (OR: 1.675, 95% CI: 1.065–2.633, P = 0.025). Immunosuppression was associated with lower risk of AKI (OR: 0.160, 95% CI: 0.029–0.886, P = 0.036). Advancing age, dependence on care, male gender and eGFR < 60 mL min −1 /1.73 m 2 increased odds of in‐hospital mortality. Conclusion: We did not identify an association between ACE‐I/ARB use and AKI, macrovascular thrombi or mortality. This supports the recommendations of the European and American Societies of Cardiology that ACE‐Is and ARBs should not be discontinued during the COVID‐19 pandemic. Abstract :